Development of a questionnaire to evaluate patients' awareness of cardiovascular disease risk in England's National Health Service Health Check preventive cardiovascular programme - Woringer, Maria; Nielsen, Jessica Jones; Zibarras, Lara; Evason, Julie; Kassianos, Angelos P.; Harris, Matthew; Majeed, Azeem; Soljak, Michael (My University, 2017)
Background The National Health Service (NHS) Health Check is a cardiovascular disease (CVD) risk assessment and management programme in England aiming to increase CVD risk awareness among people at increased risk of CVD. There is no tool to assess the effectiveness of the programme in communicating CVD risk to patients. Aims The aim of this paper was to develop a questionnaire examining patients' CVD risk awareness for use in health service research evaluations of the NHS Health Check programme. Methods We developed an 85-item questionnaire to determine patients' views of their risk of CVD. The questionnaire was based on a review of the relevant literature. After review by an expert panel and focus group discussion, 22 items were dropped and 2 new items were added. The resulting 65-item questionnaire with satisfactory content validity (content validity indices≥0.80) and face validity was tested on 110 NHS Health Check attendees in primary care in a cross-sectional study between 21 May 2014 and 28 July 2014. Results Following analyses of data, we reduced the questionnaire from 65 to 26 items. The 26-item questionnaire constitutes four scales: Knowledge of CVD Risk and Prevention, Perceived Risk of Heart Attack/Stroke, Perceived Benefits and Intention to Change Behaviour and Healthy Eating Intentions. Perceived Risk (Cronbach's α=0.85) and Perceived Benefits and Intention to Change Behaviour (Cronbach's α=0.82) have satisfactory reliability (Cronbach's α≥0.70). Healthy Eating Intentions (Cronbach's α=0.56) is below minimum threshold for reliability but acceptable for a three-item scale. Conclusions The resulting questionnaire, with satisfactory reliability and validity, may be used in assessing patients' awareness of CVD risk among NHS Health Check attendees.
Keywords: Cardiovascular disease; Risk assessment; Questionnaire; Primary prevention